Examination of testicular lumicrine regulation of activins and immunoregulatory genes in the epididymal caput. (31st August 2021) - Wijayarathna, Rukmali; Genovese, Rosemary; Meinhardt, Andreas; Loveland, Kate L; Groome, Nigel P; Hinton, Barry T; Hedger, Mark P
Abstract: Background: Immunoregulatory genes encoding activin A ( Inhba ) and B ( Inhbb ), and indolamine 2, 3‐dioxygenase‐1 ( Ido1 ) are highly expressed in the murine caput epididymidis, which also has a network of intraepithelial mononuclear phagocytes. This environment is postulated to promote immunological tolerance to epididymal sperm. The factors regulating the immunoregulatory agents in the epididymal caput are poorly understood. Objectives: This study aimed to investigate the potential role of testicular lumicrine factors in regulating activin and other immune‐related genes in the caput epididymidis. Materials and methods: The efferent ducts in adult C57/Bl6 mice were exposed and ligated bilaterally. Serum and tissues were collected seven days later. Animals with bilateral sham ligation and animals with no ligations (collectively referred to as the "intact" group) were used as controls. Results: Pressure‐induced seminiferous epithelial damage due to intratubular fluid accumulation was observed in all ligated testes. Testicular inhibin was significantly increased and testosterone was elevated in some animals following bilateral ligation, but serum testosterone, serum LH, and serum inhibin were normal. Ligation caused epithelial regression in the initial segment, with similar but less severe effects in other caput segments. Activin A staining by immunohistochemistry in the epithelium was reduced in bilateral ligation, particularly in the initial segment, with moderately reduced staining intensity in the rest of the caput. Inhba expression within the caput was not significantly affected by bilateral ligation, but Inhbb was reduced by more than 60%. Transcripts encoding the macrophage‐specific receptor Cx3cr1 were significantly reduced following bilateral ligation, but other immune cell markers, Ido1, and inflammatory genes were unaffected. Conclusion: These data indicate that testicular lumicrine secretion regulates several genes that are preferentially expressed in the initial segment, but has marginal effects on genes such as those encoding activin A and IDO1, which are expressed more widely in the caput.